Membangun Karakter “Genius” Anak Tetap Belajar Dari Rumah Selama Pandemi Covid - 19 Pada Sekolah Suta Dharma Ubud Gianyar - I Gusti Ayu Suasthi; Ida Bagus Putu Eka Suadnyana (Cetta: Jurnal Ilmu Pendidikan, 2020)
This scientific paper discusses Building the "Genius" Character of Children Keep Learning from Home During the Covid - 19 Pandemic at Suta Dharma School, Ubud, Gianyar. In addition to document study, the research data were obtained through observation and interviews with nine informants, namely teachers, students, parents of students at Suta Dharma Ubud Gianyar Elementary School. The collected data is then processed and presented in descriptive-qualitative form. The results of the study show that: First, Learning From Home (BDR) during the Covid-19 pandemic has been implemented at the Suta Dharma Ubud Gianyar Elementary School. The urgent online-based home learning is applied as part of implementing a policy that guides children's rights to continue learning and get meaningful and so that students have spiritual intelligence, social attitudes, knowledge, and skills in living life. Second, Learning From Home (BDR) has implications for (1) agile character based on a healthy physique so that students are more agile, agile, agile, nimble, fast, tough, the spirit of never giving up in taking an action, (2) the empathy attitude of the students develops caring others with sincere affection, (3) children dare to realize their dreams through channeling their own interest / potential talents, (4) children develop with superior character, spiritual intelligence and intelligent social attitudes uphold moral values, (5) children grow and get used to with a healthy lifestyle, implementing health protocols during the Covid-19 pandemic.